Low-grade serous carcinoma (mullerian/ovarian type) of the paratestis presenting as diffuse metastatic disease of unknown origin: Case report of an uncommon tumor with an unusual presentation - Alexander Filatenkov, MD; Amanda Strickland, MD; Matthew Karpowicz, DO; Franto Francis, MD PhD (Elsevier, 2018)
Low-grade (papillary) serous carcinoma of ovarian type is rare in males and histologically identical to low-grade serous carcinomas in female patients. We present a case of paratesticular low-grade serous carcinoma in a 42year old male, with the highly unusual initial presentation as diffuse metastatic disease in the abdomen. Imaging revealed a cystic lesion of the right testis/hemiscrotum. Biopsy of the abdominal metastasis and subsequent right orchiectomy specimen showed invasive papillary serous carcinoma, low grade, with prominent psammomatous calcifications. Immunohistochemically, both tumors were positive for PAX8, WT-1, CA-125 and cytokeratin CK7, and negative for mesothelioma markers (calretinin, D2-40) and CD10. The main differential diagnoses for this tumor include mesothelioma of tunica vaginalis, adenocarcinoma of rete testis/epididymis and metastases. Although rare as an initial presentation, ovarian type serous carcinoma of the paratestis should be included in the differential diagnosis in males with abdominal metastases that show papillary architecture, psamommatous calcifications and PAX8 immunoreactivity.